2020
DOI: 10.3390/nu12113391
|View full text |Cite
|
Sign up to set email alerts
|

Mildly Pasteurized Whey Protein Promotes Gut Tolerance in Immature Piglets Compared with Extensively Heated Whey Protein

Abstract: Human milk is the optimal diet for infant development, but infant milk formula (IMF) must be available as an alternative. To develop high-quality IMF, bovine milk processing is required to ensure microbial safety and to obtain a protein composition that mimics human milk. However, processing can impact the quality of milk proteins, which can influence gastro-intestinal (GI) tolerance by changing digestion, transit time and/or absorption. The aim of this study was to evaluate the impact of structural changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
2
6
0
1
Order By: Relevance
“…This study has shown that MEM-IMF digestion results in smaller curd particles, and a higher detection of primary amines, both of which should result in faster gastric emptying in vivo. [40][41][42][43] Navis et al 44 fed piglets using mildly pasteurized whey protein concentration (WPC) or extensively heated WPC. In line with our in vitro results, they demonstrated a higher gastric content in piglets receiving extensively heated WPC compared with piglets receiving mildly pasteurized WPC, which suggests delayed and/or incomplete gastric emptying in piglets fed extensively heated WPC.…”
Section: Papermentioning
confidence: 99%
“…This study has shown that MEM-IMF digestion results in smaller curd particles, and a higher detection of primary amines, both of which should result in faster gastric emptying in vivo. [40][41][42][43] Navis et al 44 fed piglets using mildly pasteurized whey protein concentration (WPC) or extensively heated WPC. In line with our in vitro results, they demonstrated a higher gastric content in piglets receiving extensively heated WPC compared with piglets receiving mildly pasteurized WPC, which suggests delayed and/or incomplete gastric emptying in piglets fed extensively heated WPC.…”
Section: Papermentioning
confidence: 99%
“…There are similar challenges in the preservation of the natural bioactivity of human or bovine milk concentrates. In NEC-sensitive preterm pigs, untreated or gently sterilized (ultraviolet-light lower-temperature sterilization) human donor milk or bovine whey protein concentrates have superior effects to protect against NEC, intestinal inflammation and systemic infections, relative to products subjected to more intense heat [ 225 , 253 , 279 , 280 ]. The same may be true for BC.…”
Section: Processing Of Bovine Colostrum For Use In Pediatricsmentioning
confidence: 99%
“…The factors in BC that support gut development, immunity and survival in other species are heat-sensitive. When whey protein concentrates are severely heated (80–85 °C, 20–30 min), a reduction in gut-protective effects is observed [ 279 , 280 ]. In contrast, raw, frozen, and mildly heat-treated BC may retain its bioactivity to protect against gut disorders and inflammation, as demonstrated in newborn term pigs [ 144 , 224 , 283 , 284 ].…”
Section: Processing Of Bovine Colostrum For Use In Pediatricsmentioning
confidence: 99%
“…Primarily, the bioactivity and anti-inflammatory or immunomodulating properties are substantially dependent on the native state of the whey proteins [ 11 , 12 , 13 ]. From a nutritional perspective, it is reported that whey proteins in their native states promote gastro-intestinal tolerance and maturation of infants [ 14 , 15 ]. Furthermore, Abbring et al [ 16 , 17 ] showed that native whey protein has a lower allergenicity than the processed, i.e., heat-treated, equivalent.…”
Section: Introductionmentioning
confidence: 99%